Efficacy of THN201, a Combination of Donepezil and Mefloquine, to Reverse Neurocognitive Deficits in Alzheimer’s Disease - Droguerre, Marine; Duchêne, Adeline; Picoli, Christèle; Portal, Benjamin; Lejards, Camille; Guiard, Bruno P.; Meunier, Johann; Villard, Vanessa; Déglon, Nicole; Hamon, Michel; Mouthon, Franck; Charvériat, Mathieu (Frontiers in Neuroscience, 2020)
Donepezil is an acetylcholinesterase inhibitor used in Alzheimer's disease to restore cognitive functions, but is endowed with limited efficacy. Recent studies pointed out the implication of astroglial networks in cognitive processes, notably via astrocyte connexins, proteins involved in gap junction intercellular communications. Hence, we investigated the impact on cognition of pharmacological or genetic modulations of those astrocyte connexins during donepezil challenge in two rodent models of Alzheimer's disease-like memory deficits. We demonstrated that the connexin modulator mefloquine significantly enhanced the procognitive effect of donepezil in both models. In parallel, we demonstrated that mefloquine potentiated donepezil-induced release of acetylcholine in hippocampus. Finally, local genetic silencing of astrocyte connexins in the hippocampus was also found to enhance the procognitive effect of donepezil, pointing out the importance of connexin-dependent astrocyte networks in memory processes.